Non-additive modulation of synaptic transmission by serotonin, adenosine, and cholinergic modulators in the sensory thalamus - Yang, Ya-Chin; Hu, Chun-Chang; Lai, Yi-Chen (Frontiers in Cellular Neuroscience, 2015)
The thalamus relays sensory information to the cortex. Oscillatory activities of the thalamocortical network are modulated by monoamines, acetylcholine, and adenosine, and could be the key features characteristic of different vigilance states. Although the thalamus is almost always subjective to the actions of more than just one neuromodulator, reports on the modulatory effect of coexisting neuromodulators on thalamic synaptic transmission are unexpectedly scarce. We found that either monoamine or adenosine decreases retinothalamic synaptic strength and short-term depression, whereas cholinergic modulators generally enhance postsynaptic response to presynaptic activity. However, combinations of different modulators tend to produce non-additive effect, not predictable based on the action of one single modulator. Acetylcholine, acting via nicotinic receptors, can interact with either serotonin or adenosine to abolish most short-term synaptic depression. Moreover, the coexistence of adenosine and monoamine, with or without acetylcholine, results in robustly decreased synaptic strength and transforms short-term synaptic depression to facilitation. These findings are consistent with a view that acetylcholine is essential for an “enriched” sensory flow through the thalamus, and the flow is trimmed down by concomitant monoamine or adenosine (presumably for the wakefulness and rapid-eye movement, or REM, sleep state, respectively). In contrast, concomitant adenosine and monoamine would lead to a markedly “deprived” (and high-pass filtered) sensory flow, and thus the dramatic decrease of monoamine may constitute the essential demarcation between non-REM and REM sleep. The collective actions of different neuromodulators on thalamic synaptic transmission thus could be essential for the understanding of network responsiveness in different vigilance states.